Decoding the Role of Astrocytes in the Entorhinal Cortex in Alzheimer’s Disease Using High-Dimensional Single-Nucleus RNA Sequencing Data and Next-Generation Knowledge Discovery Methodologies: Focus on Drugs and Natural Product Remedies for Dementia - Pushparaj, Peter Natesan; Kalamegam, Gauthaman; Wali Sait, Khalid Hussain; Rasool, Mahmood (Frontiers in Pharmacology, 2022)
Introduction: Alzheimer's disease (AD) is a major cause of the development of cognitive decline and dementia. AD and related dementias (ADRD) are the largest contributors to the enormous burden of morbidity and mortality worldwide. Objective: To decipher the role of astrocytes in the entorhinal cortex of AD patients using single nuclear RNA sequencing (snRNASeq) datasets from the Single Cell RNA-seq Database for Alzheimer's Disease (scREAD) database originally derived from astrocytes, isolated from the entorhinal cortex of the AD brain and healthy brain to decipher disease-specific signaling pathways as well as drugs and natural products that might reverse the AD specific signatures in astrocytes. Methods: We used snRNASeq datasets from the scREAD database originally derived from astrocytes isolated from the entorhinal cortex of the AD brain and healthy brain from the Gene Expression Omnibus (GEO) (GSE138852 & GSE147528) and analyzed them using Next-Generation Knowledge Discovery Platforms (NGKD). scREAD is a user-friendly open-source interface available at https://bmbls.bmi.osumc.edu/ scread/ that enables more discovery-oriented strategies. scRNASeq data and metadata can also be visualized and downloaded via an interactive web application at adsn.ddnetbio.com. Differentially expressed genes (DEGs) for each snRNASeq dataset were analyzed using iPathwayGuide to compare and derive disease-specific pathways, gene ontologies, and in silico predictions of drugs and natural products that regulate AD -specific signatures in astrocytes. In addition, DEGs were analyzed using the L1000FWD and L1000CDS2 signature search programming interfaces (APIs) to identify additional drugs and natural products that mimic or reverse AD -specific gene signatures in astrocytes. Results: We found that PI3K/AKT signaling, Wnt signaling, interaction pathways between neuroactive ligands and receptors, neurodegeneration pathways, etc. were significantly impaired in astrocytes from the entorhinal cortex of AD patients. Biological processes such as glutamate receptor signaling pathway, regulation of synapse organization, cell-cell adhesion via plasma membrane adhesion molecules and chylomicrons were negatively enriched in astrocytes from entorhinal cortex of AD patients. Conclusions: The present study demonstrates an innovative approach to use NGKD platforms to find unique disease-associated pathways and specific synthetic drugs and natural products that can potentially reverse AD and ADRD-associated gene signatures.